2022
DOI: 10.3390/jcm11071977
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shockwave Therapy in the Treatment of Nonunion in Long Bones: A Systematic Review and Meta-Analysis

Abstract: Background: Nonunion is one of the most challenging problems in the field of orthopedics. The aim of this study was to perform a systematic review of the literature to evaluate the effectiveness of extracorporeal shockwave therapy (ESWT) in the treatment of nonunion in long bones. Methods: We conducted a search of three databases (PubMed, Scopus, and Web of Science) and found 646 total publications, of which 23 met our inclusion criteria. Results: Out of 1200 total long bone nonunions, 876 (73%) healed after b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…A variety of bone and muscle diseases have been treated with ESWT, including external epicondylitis of the humerus, plantar fasciitis, bone nonunion. [29][30][31] Recently, ESWT have been investigated, but the mechanisms of action are not well understood. According to general knowledge, extracorporeal shock waves induce characteristic changes within living tissues due to the conversion of mechanical signals into biochemical signals.…”
Section: Implication and Explanation Of Findingsmentioning
confidence: 99%
“…A variety of bone and muscle diseases have been treated with ESWT, including external epicondylitis of the humerus, plantar fasciitis, bone nonunion. [29][30][31] Recently, ESWT have been investigated, but the mechanisms of action are not well understood. According to general knowledge, extracorporeal shock waves induce characteristic changes within living tissues due to the conversion of mechanical signals into biochemical signals.…”
Section: Implication and Explanation Of Findingsmentioning
confidence: 99%
“…Within this frame, the use of ESWT has gathered increasing attention due to its biological potential in enhancing osteogenesis ( 12 , 13 ) and thus promoting fracture healing ( 5 , 7 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence in basic research demonstrates that shock wave stimulation generates its effect in tissue via mechanotransduction which triggers several endogenous bone regeneration processes via cell proliferation, differentiation, and migration ( 15 17 ). Furthermore, there are several clinical observational studies on the beneficial effects of ESWT on bone healing ( 7 , 13 , 14 , 18 , 19 ). For instance, a very recent systematic review of the literature conducted on three main databases (i.e., PubMed, Scopus, and Web of Science) showed that out of 1200 total long bone nonunions, 876 (73%) healed after being treated with ESWT, with hypertrophic cases achieving 3-fold higher healing rates when compared to oligotrophic or atrophic cases ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous techniques have been proposed for the treatment of femoral shaft pseudarthrosis, including electromagnetic fields [7], low-intensity ultrasound [8], extracorporeal shock wave therapy (ESWT) [9], external fixators [10] and osteosynthesis with plate and screws [11]. Moreover, several studies have reported positive results after the treatment of non-union of the femur with single or double plate fixation combined with autologous bone graft [12,13].…”
Section: Introductionmentioning
confidence: 99%